Estimating the Permeability of Naturally Structured Soil From Percolation Theory and Pore Space Characteristics Imaged by X‐Ray. Issue 11 (23rd November 2018) - Koestel, John; Dathe, Annette; Skaggs, Todd H.; Klakegg, Ove; Ahmad, Muhammad Arslan; Babko, Maryia; Giménez, Daniel; Farkas, Csilla; Nemes, Attila; Jarvis, Nicholas
Abstract: The saturated hydraulic conductivity of soil, K s, is a critical parameter in hydrological models that remains notoriously difficult to predict. In this study, we test the capability of a model based on percolation theory and critical path analysis to estimate K s measured on 95 undisturbed soil cores collected from contrasting soil types. One parameter (the pore geometry factor) was derived by model fitting, while the remaining two parameters (the critical pore diameter, d c, and the effective porosity) were derived from X‐ray computed tomography measurements. The model gave a highly significant fit to the K s measurements ( p  < 0.0001) although only ~47% of the variation was explained and the fitted pore geometry factor was approximately 1 to 2 orders of magnitude larger than various theoretical values obtained for idealized porous media and pore network models. Apart from assumptions in the model that might not hold in reality, this could also be attributed to experimental error induced by, for example, air entrapment and changes in the soil pore structure occurring during sample presaturation and the measurement of K s . Variation in the critical pore diameter, d c, was the dominant source of variation in K s, which suggests that d c is a suitable length scale for predicting soil permeability. Thus, from the point of view of pedotransfer functions, it could be worthwhile to direct future research toward exploring the correlations of d c with basic soil properties and site attributes. Key Points: Reliable methods to predict permeability of naturally structured soils are currently lacking A percolation‐based method applied to X‐ray scanning data explained 47% of the variation in the measured permeability of 95 soil samples Variation in permeability was controlled by the critical pore diameter: the estimated effective porosity did not contribute significantly